VARK-based Chemistry Learning to Improve Students’ Critical Thinking Skills in Learning Molecular Geometry - Ade Gunawan; Leny Heliawati; Anna Permanasari (Yayasan Keluarga Guru Mandiri, 2023)
Learning that does not accommodate the learning styles of all students will experience boredom and a decrease in the critical level of students. This study aims to determine the effect of VARK learning style-based chemistry learning on improving students' critical thinking skills. The study used a quantitative method with a pre-experimental design and one group pretest-posttest design. The research was conducted on 65 students of the State Islamic Senior High School in Bogor. The instrument used was an essay test of ten questions that met the criteria for critical thinking indicators. The instrument trials used were validity and reliability tests. Next, the Paired T-Test and N-Gain Tests were carried out. Based on the Paired T-Test, a significance value of 0.00 was obtained, indicating that Ho was rejected, so there were differences in students' critical thinking skills before and after the VARK-based chemistry learning was implemented. The results of the N-Gain test increased students' critical thinking skills on average by 0.68 in the moderate category. This study concludes that VARK-based chemistry learning on molecular geometry material can improve students' critical thinking skills.Â Â